Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 2 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Accompanists; Composers; Librettists; Music; Musical performances; Musicians & conductors; Opera; Singers

Colloquy/Débat: Violet Archer, Jean Coulthard, and Barbara Pentland Remembered - Deaville, James (Canadian University Music Review, 2000)
In a bizarre coincidence, three important Canadian women composers from the same generation recently died within five weeks of each other: Barbara Pentland on 6 February 2000, Violet Archer on 22 February 2000, and Jean Coulthard on 9 March 2000. As a tribute to their lives and work, this colloquy gathers remembrances of them by friends and colleagues, ranging from brief anecdotes to extended memoirs. It is thus a collection of primary documents, which yield many new insights into the lives of our composers, ranging from personal habits to the way they taught composition.
Keywords: Canadian music; Careers; Composers; Composition; Music